Exploring Monotopic quinone reductases - Sousa, Filipe Medina (2021)
"Respiratory chains are groups of membrane bound enzymes which generate a membrane electrochemical potential by coupling an exergonic reaction to the translocation of charges (electrons or ions, H+ or Na+) across the membrane. Quinone reductases are considered the electron entry point of respiratory chains as they connect the different catabolic pathways from the soluble cytoplasmic reactions to the membrane bound respiratory chains. Quinone reductases can be classified in transmembrane or monotopic (placed at a single side of the lipid bilayer), with only the first ones directly contributing to the generation of the membrane electrochemical potential. Currently, 20 different “electron donor”:quinone oxidoreductase enzymatic activities have been described, from which 10 are monotopic.(...)"